2019
DOI: 10.1002/pd.5525
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐based biomarkers in the maternal circulation associated with fetal growth restriction

Abstract: Fetal growth restriction (FGR) is associated with threefold to fourfold increased risk of stillbirth. Identifying FGR, through its commonly used surrogate-the small-forgestational-age (SGA, estimated fetal weight and/or abdominal circumference <10th centile) fetus-and instituting fetal surveillance and timely delivery decrease stillbirth risk. Methods available to clinicians for antenatal identification of SGA fetuses have surprisingly poor sensitivity. About 80% of cases remain undetected.Measuring the symphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 98 publications
(158 reference statements)
0
15
0
Order By: Relevance
“…71 As analysis of fetal circulating DNA, RNA and proteins in the maternal blood advances, it is possible that fetal laboratory-based AEs will be developed to further assess fetal well-being. 72,73 The goal of a standardised AE severity scale is to reduce subjectivity in severity assessments and thus reduce interobserver variability. We are currently planning prospective validation studies of agreement among observers in different countries for the generic and specific severity criteria for maternal and fetal AEs.…”
Section: Discussionmentioning
confidence: 99%
“…71 As analysis of fetal circulating DNA, RNA and proteins in the maternal blood advances, it is possible that fetal laboratory-based AEs will be developed to further assess fetal well-being. 72,73 The goal of a standardised AE severity scale is to reduce subjectivity in severity assessments and thus reduce interobserver variability. We are currently planning prospective validation studies of agreement among observers in different countries for the generic and specific severity criteria for maternal and fetal AEs.…”
Section: Discussionmentioning
confidence: 99%
“…SGA fetuses are at three to four times higher risk for stillbirth than appropriate weight fetuses, which signifies that early prediction of SGA and intrauterine growth restriction is crucial in prevention 2,3 . For this reason, researchers are trying to find possible Copyright 2021 KEI Journals.…”
Section: Introductionmentioning
confidence: 99%
“…http://journals.ke-i.org/index.php/mra biomarkers with a strong predictive value. Pregnancy-associated plasma protein-A (PAPP-A) and human placental growth factor (hPGH) were linked to SGA but showed little clinical value when evaluated alone 2 . Insulinlike growth factor-1 (IGF-1) was proposed as a possible marker for several pregnancy outcomes, including preeclampsia and SGA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cerebral–placental ratio (CPR) and cerebral–placental–uterine ratio (CPUR) were identified as novel predictors, and at a 90% specificity, a low CPUR had sensitivities of 50% for birthweight <10th centile ( 8 ). Additionally, maternal serum biomarkers are novel approaches to screening the suspected FGR (PIGF, sFlt-1), but the specific effectiveness needs more studies for verification ( 7 , 9 ). A study showed that 82% of stillbirths with FGR were not detected in the prenatal period ( 9 ) so accurate identification is important.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, maternal serum biomarkers are novel approaches to screening the suspected FGR (PIGF, sFlt-1), but the specific effectiveness needs more studies for verification ( 7 , 9 ). A study showed that 82% of stillbirths with FGR were not detected in the prenatal period ( 9 ) so accurate identification is important. Ultrasonic Doppler is the main means of monitoring.…”
Section: Introductionmentioning
confidence: 99%